Supreme Audit Institutions Independence Index : 2021 Global Synthesis Report - World Bank (World Bank, Washington, DC, 2021)
This report aims to inform and better equip World Bank task teams and development partners to support the strengthening of Supreme Audit Institutions (SAIs) in client countries. It also aims to help focus the ongoing collaboration between the International Organisation of Supreme Audit Institution (INTOSAI) and development agencies to address the intractable SAI independence issue. The report also responds to yearnings of several development partners to better understand the degree of SAI independence in countries and regions.